ANALISIS PENGARUH KUALITAS DAN TARIF LAYANAN TERHADAP LOYALITAS PENUMPANG MELALUI KEPUASAN PENUMPANG PADA LAYANAN TRANSPORTASI LAUT - Nelson S. Pangaribuan; Yenita (GoAcademica Research dan Publishing, 2022)
This research was conducted to determine the factors that influence passenger loyalty in water transportation. The research approach used was a quantitative approach. The research data is primary data obtained through a survey technique. The data that has been collected was then analyzed by path analysis. The research results showed that: 1) service quality has a significant and positive effect on passenger satisfaction; 2) tarrif has a significant and positive effect on passenger satisfaction; 3) service quality has a significant and positive effect on passenger loyalty; 4) tarrif has a positive but not significant effect on passenger loyalty; 5) passenger satisfaction has a significant and positive effect on passenger loyalty; 6) service quality has a significant effect on passenger loyalty through passenger satisfaction, as well as; 7) tarrif has a positive and significant effect on passenger loyalty through passenger satisfaction at PT ASDP route Merak-Bakauheni.